2019
DOI: 10.1371/journal.pone.0226542
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin reduces the inhibitory effect of osmotic stress on photosynthesis in soybean

Abstract: Understanding the relationship between exogenous melatonin and water deficit stress is crucial for achieving high yields and alleviating the effects of water deficit stress on soybean (Glycine max (L.) Merrill) plants in agriculture. This study investigated the effects of exogenous melatonin on soybean photosynthetic capacity under water deficit stress induced by polyethylene glycol (PEG) 6000. We conducted a potting experiment in 2018 using the soybean (Glycine max L. Merrill) cultivar Suinong 26. We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 71 publications
(76 reference statements)
1
30
0
Order By: Relevance
“…In addition to the genetic evidence, exogenous melatonin treatment conferred stress tolerance to a wide range of biotic and abiotic stressors, including viral attack [ 8 , 54 , 55 ]. In addition to being involved in defense responses, melatonin is also involved in plant growth in conjunction with photosynthesis when plants were challenged with abiotic stresses [ 20 , 56 ]. For example, melatonin treatment enhanced soybean growth by increasing PSI- and PSII-related genes and increased the rate of photosynthesis in Chinese hickory and grape seedlings upon stresses [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the genetic evidence, exogenous melatonin treatment conferred stress tolerance to a wide range of biotic and abiotic stressors, including viral attack [ 8 , 54 , 55 ]. In addition to being involved in defense responses, melatonin is also involved in plant growth in conjunction with photosynthesis when plants were challenged with abiotic stresses [ 20 , 56 ]. For example, melatonin treatment enhanced soybean growth by increasing PSI- and PSII-related genes and increased the rate of photosynthesis in Chinese hickory and grape seedlings upon stresses [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, melatonin enhances plant resistance via higher stomatal conductance [ 42 ], higher cell turgor and water holding capacity [ 65 ], and stomatal opening regulation [ 77 ]. Consequently, the whole plant status is enhanced, including seed germination efficiency [ 47 ], root generation vitality and strength [ 61 ], growth and flowering [ 36 , 50 ], visual quality [ 65 ], seed yield [ 38 ], leaf senescence alleviation [ 54 ], and quick recovery after rehydration [ 59 ].…”
Section: Melatonin-induced Drought Stress Tolerancementioning
confidence: 99%
“…Photosynthesis is the key process necessary for the growth and development of higher plants; it is also one of the processes most sensitive to waterlogging stress (Sterling et al 2019, Zhang et al 2019b. The preliminary experiments in this study revealed that waterlogging stress reduced PN, E, gs, and Ci, and PN decreased more rapidly in SY-XT1 than that in SY-MY13 ( Fig.…”
Section: Discussionmentioning
confidence: 61%